2016
DOI: 10.15294/kemas.v11i2.4495
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Somatotype, Status Gizi, Dan Dietary Atlet Remaja Stop and Go Sports

Abstract: <p>Kelelahan akibat durasi permainan yang panjang dengan intensitas gerakan cepat dan tiba-tiba menjadi masalah yang paling umum terjadi pada atlet <em>stop and go sports</em> . Peran zat gizi dalam upaya pencapaian performa maksimal sering dilupakan. Bersama dengan latihan yang intensif, asupan yang adekuat dapat membentuk <em>somatotype</em> yang juga dapat membantu performa. Tujuan penelitian ini adalah mengidentifikasi <em>somatotype</em> serta mengevaluasi asupan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 6 publications
(8 reference statements)
0
4
0
9
Order By: Relevance
“…This habit becomes more risky if the person does not outfits that covers the entire body or use mosquito repellent before going out of the house. The percentage of nightly outdoor activities was higher in the case group (51.7%) than the control group (20.7%), due to increased risk of contact with the mosquitoes (Penggalih et al, 2016).…”
Section: Resultsmentioning
confidence: 82%
“…This habit becomes more risky if the person does not outfits that covers the entire body or use mosquito repellent before going out of the house. The percentage of nightly outdoor activities was higher in the case group (51.7%) than the control group (20.7%), due to increased risk of contact with the mosquitoes (Penggalih et al, 2016).…”
Section: Resultsmentioning
confidence: 82%
“…Preliminary study also showed that there was no individual dietary planning of athletes. This can be a problem because the energy needs of every athletes were different (Puttuck, 2014;Penggalih, 2016). The preliminary study also showed that several energy input and output imbalance were due to lack availability of food in the night, bad taste of food, and the athlete's lack of knowledge about their energy needs.…”
Section: Methodsmentioning
confidence: 97%
“…Kemampuan serangan terutama serangan tangan hanya terlihat sebagai pancingan untuk melakukan serangan lanjutan dan serangan tangan yang dilakukan atlet tidak ada yang menjadi sebuah poin yang bisa mendukung kemenangan. Penggalih et al, (2016) mengatakan pada cabang olahraga bersifat stop and go salah satunya adalah cabang olahraga pencak silat menuntut atlet untuk selalu siap karena serangan berintensitas tinggi dapat datang kapan saja walaupun tingginya tingkat intensitas gerakan permainan tidak terjadi sepanjang permainan.…”
Section: Pendahuluanunclassified
“…Program latihan yang telah diterapkan selama di Training Center (TC) telah melaksanakan serangan-serangan termasuk serangan tangan tetapi masih banyak kekurangan yang dialami atlet saat bertanding sehingga kurang optimalnya serangan tangan yang dilakukan. Hal ini bisa terlihat pada permasalahan utama yang sering ditemui oleh atlet adalah stamina dan ketahanan tubuh (Penggalih et al, 2016).…”
Section: Pendahuluanunclassified